#ShePersisted, Mitch: a memetic critical discourse analysis on an attempted Instagram feminist revolution. Issue 7 (2nd October 2020) - Boling, Kelli S.
ABSTRACT: Through feminist critical discourse analysis, this article examines the memetic discourse (image-driven conversation) via feminist standpoint theory on Instagram during the digital feminist movement, #ShePersisted. This study explores the digital communications of a networked community during a time of attempted revolution and contributes to the conversation of how future feminist movements (both on and offline), can lead the conversation regarding feminist issues. Examining the first 48 hours of the discourse, this study found that the conversation evolved from the original Coretta Scott King letter to what Elizabeth Warren did, to how the news media presented the situation, to the personal story each participant wanted to tell. Analyzing 2, 005 memes from February 8 and 9, 2017, this study found that the most prominent theme was "inspiration, " accounting for 73.3% (1, 469) of posts. Not only did the online discourse attempt to elevate the national conversation regarding feminist issues, but the use of the hashtag spurred street-level protests and letter-writing campaigns as well, mirroring the path other successful digital feminist revolts. Ultimately, this study shows how political power impacts women and what can happen in a digital environment when marginalized communities connect and transfer the conversation from their computer screens to the streets.